Promoting work motivation in organizations: Should employee involvement in organizational leadership become a new tool in the organizational psychologists' armoury? - Wegge, J. (2014)
What are the best interventions that Work and Organizational Psychology offers today for promoting high work motivation in organizations? This paper seeks to answer this question in two steps. First, we briefly summarize the main findings from 26 meta-analyses concerned with traditional practices such as goal setting, feedback, work design, financial incentives, or training. These practices can improve both organizational performance and the well-being of organizational members. Second, we examine in more depth a new, increasingly important high performance work practice: Employee involvement in organizational leadership (EIOL). This approach is built on theories focusing on organizational participation, shared leadership, and organizational democracy. We also illustrate recently constructed measurement instruments for assessing these constructs. This synopsis leads us to the development of a new integrative, multilevel model of EIOL. The model includes several mediator (e.g., knowledge exchange) and moderator variables (e.g., self-leadership competencies of actors) that explain why and when this approach is effective. We conclude that future research should focus on cross-level interactions of different forms of organizational participation, shared leadership, and organizational democracy, and seek to identify the processes mediating their interplay.